(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
Seven bryozoan species are described from the shallow-water Aisemont and Lambermont formations (upper rhenana Conodont zone, upper Frasnian) in southern Belgium. The studied interval is situated between the lower and upper Kellwasser events. Among the recognized taxa two species are new: Triznotrypa potii n. sp. and Isostylus veserensis n. sp. In addition, the following species were identified in this assemblage: Fistulipora pavimenta Bigey, 1988, Canutrypa hemispheroidea (Yang, 1954), Eostenopora conspersa Volkova, 1974, Leptotrypella radiata Bigey, 1988, and Anastomopora inflata (Bigey, 1988). The studied bryozoan assemblage of the Frasnian age shows palaeogeographic connections to Iran, Russia (Altai) and Afghanistan. Most of them are documented for the first time in this area and it provides important knowledge of the distribution of bryozoans in the late Frasnian and near the Frasnian-Famennian boundary.